Effect of phonon scattering by substitutional and structural defects on thermal conductivity of 2D graphene. (26th June 2018) - Lee, Byoung Seo
Abstract: The ability to tailor the thermal conductivity of graphene by introducing crystalline defects has attracted considerable research attention. In this study, nonequilibrium molecular dynamics calculation is used to investigate the effect of crystalline defects on the thermal conductivity of 2D graphene. The defects considered include substitutional nitrogen and silicon, pure structural single vacancy and Stone–Wales defects, and structurally different pyridinic nitrogen. In particular, this study focuses on the unique phonon scattering behaviors arising from the low dimensionality of graphene. The results reveal that the low dimensionality of graphene has a negligible effect on phonon scattering in substitutionally defected graphene, for which the Klemens scattering model is accurate without the need for any corrections. The substitutional silicon defect leads to more effective reduction of the thermal conductivity than the structural defects because of the effect of change in the hybridization and the mass on the scattering. Almost equal reductions are observed for the two structural defects, the scattering strengths of which are significantly weakened by the two dimensionality of graphene. Callaway analysis of the vacancy scattering reveals that even with the perturbation of the vacancy, the 2D honeycomb structure preserves considerable phonon stability compared with a 3D material. In addition, the absence of mass deficiency for the Stone–Wales defect suggests that the contribution of mass deficiency is minimized for structural defects of graphene. Finally, opposite to the findings for the substitutional nitrogen defect, the introduction of pyridinic nitrogen leads to further reduction of the thermal conductivity compared with that for a single vacancy defect.